Participation and Indigenous Peoples - World Bank (World Bank, Washington, DC, 2012)
The characteristics of indigenous groups make participatory approaches especially critical to safeguarding their interests int he development process. Such approaches, recognizing the right of indigenous peoples to participate actively in planning their own futures, are supported by major donors and international organizations, including the World Bank, but have proved very difficult to implement. They call for changes in attitudes, policies and legislation to address the key issues: recognizing rights to land and nautral resources, ensuring culturally appropriate procedures for consultations and communication; and building on the strengths of traditional lifestyles and institutions.